Dampak Kepemimpinan Transformasional Terhadap Kepuasan Kerja dan Kinerja Karyawan Generasi Z: Studi Peran Intervening Kepercayaan pada Pemimpin - Sadewa, Robby Rahadyan; Siti Nurlaela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of transformational leadership on job satisfaction and job performance, considering trust in the leader as a mediating variable. The sample was selected using a purposive sampling technique, with a total of 268 Generation Z employees working in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. The data were analyzed using the Structural Equation Modeling (SEM) method through Smart PLS 3.0 software. The findings indicate that transformational leadership has a significant and positive impact on trust in the leader, job satisfaction, and job performance. Furthermore, trust in the leader was proven to mediate the relationship between transformational leadership and both job satisfaction and job performance. The implications of this study highlight the crucial role of leaders in building trust to enhance employee productivity and job satisfaction, particularly among the younger workforce. This research provides both practical and theoretical insights into leadership strategies that support organizational success.